Tafsir Digital dan Hibridisasi Bahasa: Dimensi Kontekstual Q.S. Al-Jumu'ah 62:11 dalam Podcast Spotify Ngafal-Ngefeel - Achmad Sofiyul Mubarok; Abdulloh Dardum (Contemporary Quran, 2025)
The development of digital media has created a new ecosystem for the practice of interpreting the Qur’an that goes beyond conventional study forums. The podcast “Ngafal-Ngefeel” on Spotify is one manifestation of this shift, in which the sacred text is interpreted in an audio-only, dialogic format that is accessible to Millennials and Gen Z. This article analyzes how the hybridization of language in the podcast functions as a contextual hermeneutic strategy in interpreting Qur’anic Surah Al-Jumu’ah, verses 9 through 11, using Abdullah Saeed’s framework of contextual exegesis. This study demonstrates that the interpreter consistently employs a blend of Arabic, English, and popular Indonesian terms such as “distract,” “cuan,” “flash sale,” and “scroll culture” as contextualization mechanisms that bridge the historical meaning of the verses with the reality of the audience’s digital lives. Saeed’s hierarchy of values has been shown to operate simultaneously: obligatory values affirm the obligation of Friday prayer; fundamental values redefine tijarah and lahwun in the context of the contemporary economy and digital distractions; while contextual values foster ethical awareness regarding the culture of consumerism and excessive productivity. Furthermore, Spotify’s audio-only medium has been shown to create a distinctive hermeneutic character, in which the prosody of the voice, intonation, and narrative rhythm become active components in the production of religious meaning. This finding introduces audio-digital hermeneutics as a relevant typology of contemporary interpretation developed within the field of digital exegesis.